Injection Molded of Bio-Micro-Composites from Natural Fibers and Polylactic Acid - Subyakto Subyakto; Euis Hermiati; Nanang Masruchin; Ismadi Ismadi; Kurnia Wiji Prasetiyo; Wida Banar Kusumaningrum; Bambang Subiyanto (Wood Research Journal, 2011)
Green composites were needed by automotive industries because they are environmentally friendly, recyclable, lightweight and strong. Natural fibers such as bamboo and sisal are potential source of these materials and can be used as substitutes of fiber glass which is hard to recycle and not renewable.  In this experiment, bio-composites made from micro fibers of betung bamboo (Dendrocalamus asper) and sisal (Agave sisalana) mixed with a natural polymer of polylactic acid (PLA) were developed that may used for automotive application. Bamboo or sisal fibers were converted into pulp and processed using a disc refiner to produce microfibrillated cellulose (MFC) with fiber diameter around 10 µm. MFC was mixed with PLA and triacetin and dried. The mixture was processed in a mixer at temperature of 170ºC, speed of 60 rpm for 20 min. The compound mixture was removed and processed into pellets using a pelletizer at 170ºC. Pellets were processed using injection molding machine. The compositions of fibers/PLA were 10/90, 20/80, and 30/70. The mechanical properties were tested in accordance with ASTM standards. Result shown that optimum composition ratio of bamboo fibers/PLA was 20/80 which gave flexural strength of 62.30 MPa, flexural modulus of 3.89 GPa, tensile strength of 44.55 MPa, tensile modulus of 1.20 GPa, and hardness of 112.90 R. While the optimum composition ratio of sisal fibers/PLA was 30/70 which gave flexural strength of 67.83 MPa, flexural modulus of 4.43 GPa, tensile strength of 48.18 MPa, tensile modulus of 1.13 GPa, and hardness of 110.50 R.